Introdução à política educacional em tempos de barbárie - Novaes, Henrique Tahan (Editora Oficina Universitária, 2022)
The dictatorship of financial capital has produced disastrous consequences for the education of the working class. This new form of dictatorship - called globalization or the knowledge society by intellectuals on the right - allows large educational groups to earn millions of dollars daily in the educational sector, in addition to obviously reproducing the values of the capitalist mode of production. In the Brazilian case, the business-military dictatorship metamorphosed into the dictatorship of financial capital. Although the social and educational struggles of the 1980s were intense, the reins of the transition did not leave the hands of the bourgeoisie and the military, blocking the "redemocratization" of the country. The election of Collor, the neoliberal governments of FHC and even Lulism, raised the commodification of education to new levels and prevented the realization of some achievements of the 1988 Constitution. The "proclamation of the Republic" in 1889 was not accompanied by agrarian reform , former slaves were marginalized, without job opportunities, education and without a decent place to live. Anyway, education continued to be elitist and for the few. In turn, the 1930 revolution partially industrialized the country, produced a timid educational reform, but again the proposals for the massification of quality public education were aborted. Educators like Anísio Teixeira who defended the massification of public schools were marginalized and even called "communists". In countries of dependent capitalism like Brazil, chronic problems of educational policy such as underfunding of public education, precariousness of teaching work, functional illiteracy, elite higher education will not be resolved within the framework of capitalism. They can even be superficially mitigated in popular governments, but they have deep determinations that prevent their solution within the orbit of capital. In this book, we seek to address - dialoguing especially with beginners - the classic problems of Brazil - now potentiated and opened wide by the pandemic and ultraneoliberalism - that prevent the universalization of public, free and quality education, or in another sense, we seek to identify the factors that allowed Brazil a great prominence in the rankings of commodification of education and educational barbarism. Educational themes have profound determinations - generally neglected in educational debates: colonial-slavery matrix, export of commodities, large land ownership, hyper-late and fragile industrialization, underemployment and permanent counter-revolution.